Biconvex programming approach to optimization over the weakly efficient set of a multiple objective affine fractional problem - Q. Tuyen, Hoang; D. Muu, Le (Operations research letters, 2001)
We formulate the problem of optimizing a convex function over the weakly efficient set of a multicriteria affine fractional program as a special biconvex problem. We propose a decomposition algorithm for solving the latter problem. The proposed algorithm is a branch-and-bound procedure taking into account the affine fractionality of the criterion functions.